Answer:
12
Step-by-step explanation:
5(x-6)=2(x+3)
multiply
5*x and 5*6. 2*x and 2*3
5x-30=2x+6
minus 5x and 2x
3x-30=6
add 30 to 6
3x=36
divide both sides by 3 and the 3x cancels so 36÷3
x=12
Answer:
No they are equivalent
Step-by-step explanation:
3/7 =21/35
3/5=21/35
Step-by-step explanation:
log (√1000000x)
Rewrite √1000000x as (1000000x)1/2.
expand long ((1000000x)1/2) by moving 1/2
oby moving logarithm.
1/2 longth (1000000x)
Rewrite
log
(1000000x) as log(1000000)+log(x).
1/2(log(1000000)+log(x))
Logarithm base 10 of 1000000 is 6.
1/2(6+log(x))
Apply the distributive property.
1/2.6+1/2 log(x)
Cancel the common factor of 2.
3+1/2 long(x)
Combine 1/2 and log(x)
3+ long(x)/2
Answer:
B
Step-by-step explanation:
logₓ 7 = 3
x³ = 7
Take cube root both sides
![x= \sqrt[3]{7}](https://tex.z-dn.net/?f=x%3D%20%5Csqrt%5B3%5D%7B7%7D)
X^2=10
square root it
sqrt(x^2) = sqrt (10)
x= sqrt(10)
Cannot reduce more